A method for preparing sodium manganese titanium phosphate positive electrode material for sodium ion battery and vehicle

By mixing sodium, phosphorus, carbon, titanium, manganese and high entropy metal sources, and using polyarylethernitrile derivatives and sodium sulfonate derivatives as slurry binders, the preparation of manganese titanium sodium phosphate positive electrode materials is solved, and the problems of high cost and poor electrochemical performance of existing sodium ion battery positive electrode materials are achieved, achieving high rate performance and long cycle life.

CN119390038BActive Publication Date: 2025-04-15ZHEJIANG HUAYU NADIAN NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411958022.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing sodium ion battery cathode materials have problems such as high cost, difficult production and poor electrochemical performance. In particular, the high cost of metal vanadium elements and the corrosiveness of fluorine sources increase the process difficulty and production cost of the material.

Method used

A mixing method of sodium, phosphorus, carbon, titanium, manganese and high-entropy metal source is used to combine polyarylethernitrile derivatives and sodium sulfonate salt derivatives as slurry binders, and a sodium manganese titanium phosphate positive electrode material is prepared by sand milling, spray drying and high-temperature calcining.

Benefits of technology

The first cycle reversible capacity of manganese titanium sodium phosphate positive electrode material for sodium ion batteries is improved, its resistivity is reduced, and the rate performance and cycle life are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390038B_ABST
    Figure CN119390038B_ABST
Patent Text Reader

Abstract

A method for preparing a sodium manganese titanium sodium phosphate positive electrode material for a sodium ion battery and a vehicle, belonging to the technical field of synthesis of sodium ion battery positive electrode materials, specifically relates to a method for preparing a sodium manganese titanium sodium phosphate positive electrode material for a sodium ion battery; the preparation method comprises mixing a sodium source, a phosphorus source, a carbon source, a titanium source, a manganese source and a high entropy metal source, then adding a slurry binder for high-speed stirring and dispersion, and preparing a sodium manganese titanium sodium phosphate positive electrode material for a sodium ion battery through sand milling, spray drying and high-temperature calcination; the slurry binder comprises at least a polyarylether nitrile derivative, and the polyarylether nitrile derivative has sulfur and a cyano group. The present invention is a method for preparing a sodium manganese titanium sodium phosphate positive electrode material for a sodium ion battery with high first cycle reversible capacity, low resistivity, long cycle life and excellent rate performance, and the prepared sodium manganese titanium sodium phosphate positive electrode material for a sodium ion battery is used in the preparation of a vehicle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of synthesis of positive electrode materials for sodium ion batteries, and in particular to a method for preparing a sodium manganese titanium phosphate positive electrode material for sodium ion batteries. Background Art

[0002] As a new type of energy storage device, sodium-ion batteries have the advantages of low cost and high safety. They can alleviate the problem of limited development of energy storage batteries caused by the shortage of lithium resources to a certain extent. They have great development potential in the field of large-scale energy storage and are a beneficial supplement to lithium-ion batteries in this field. They will gradually replace traditional rechargeable batteries (such as lead-acid batteries and nickel-cadmium batteries), showing significant economic and environmental benefits.

[0003] At present, polyanion-type cathode materials for sodium-ion batteries have attracted much attention due to their advantages such as high operating voltage and stable three-dimensional structural framework. Among them, sodium superion conductor (NASICON)-type cathode materials have been widely reported due to their excellent electrochemical properties, such as sodium vanadium phosphate and sodium vanadium fluorophosphate. However, the metal vanadium element is expensive and highly toxic, which is not conducive to large-scale production. At the same time, the introduction of highly corrosive fluorine sources further increases the process difficulty and production cost of the material. Therefore, it is urgent to develop a method for preparing sodium manganese titanium phosphate cathode materials for sodium-ion batteries that are low-cost, easy to produce and have high sodium storage performance. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a sodium manganese titanium phosphate positive electrode material for a sodium ion battery, thereby improving the first cycle reversible capacity of the sodium manganese titanium phosphate positive electrode material for a sodium ion battery and reducing its resistivity, thereby obtaining a sodium manganese titanium phosphate positive electrode material for a sodium ion battery with excellent rate performance and long cycle life.

[0005] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0006] A method for preparing a sodium manganese titanium sodium phosphate positive electrode material for a sodium ion battery comprises the following steps: mixing a sodium source, a phosphorus source, a carbon source, a titanium source, a manganese source and a high entropy metal source, adding a slurry binder, stirring and dispersing at high speed, and performing sand milling, spray drying and high-temperature calcination to prepare the sodium manganese titanium sodium phosphate positive electrode material for the sodium ion battery; the slurry binder comprises at least a polyarylether nitrile derivative, and the polyarylether nitrile derivative has a sulfur element and a cyano group.

[0007] The present invention uses high entropy doping of calcium ions, magnesium ions, zinc ions, copper ions and aluminum ions to occupy Na 3 MnTi(PO 4 ) 3 The Mn sites in 3+The present invention also uses polyarylether nitrile derivatives as slurry binders. The polyarylether nitrile derivatives have a large number of polar cyano groups, which can form strong hydrogen bonds and dipole-dipole interactions with the hydroxyl groups on the surface of the electrode active material, thereby improving the electrochemical compatibility of the positive electrode material of the sodium ion battery, thereby improving the first cycle reversible capacity of the sodium manganese titanium phosphate positive electrode material for the sodium ion battery and reducing its resistivity.

[0008] Preferably, in the preparation of the polyarylethernitrile derivative, 2-(2,6-dichlorophenyl)-3-phenylglutaronitrile is reacted with hydroquinone and phenolsulfonphthalein to obtain the polyarylethernitrile derivative.

[0009] Preferably, the sodium source is sodium acetate, the phosphorus source is ammonium dihydrogen phosphate, and the molar ratio of the phosphorus source to the sodium source is 1:1-6.

[0010] Preferably, the carbon source comprises polyethylene glycol and sucrose, and the mass ratio of sucrose to polyethylene glycol is 1:1-2.

[0011] Preferably, the manganese source is manganese acetate, the titanium source is titanium dioxide, and the molar ratio of the titanium source to the manganese source is 1:0.5-1.0.

[0012] Preferably, the high entropy metal source includes calcium acetate, magnesium acetate, zinc oxalate, copper oxalate and aluminum nitrate.

[0013] Preferably, during the sand milling process, the sand milling speed is 1000-3000 rpm, and the processing time is 1-4 hours.

[0014] Preferably, during spray drying, the inlet air temperature is 150-250° C., the atomizer frequency is 200-400 Hz, and the feed rate is 2-5 L / h.

[0015] Preferably, in the high temperature calcination, the calcination temperature is 500-800° C. and the calcination time is 6-24 h.

[0016] Preferably, the preparation of the polyarylethernitrile derivative is specifically as follows:

[0017] Weigh 2-(2,6-dichlorophenyl)-3-phenylglutaronitrile, hydroquinone and phenolsulfonphthalein, add N-methylpyrrolidone and stir evenly, then add anhydrous potassium carbonate and toluene, react at 100-200°C for 2-5h, rotary evaporate, react at 150-250°C for 3-7h, add a precipitant, precipitate a white solid, wash with deionized water 2-5 times, and vacuum dry to obtain a polyarylether nitrile derivative.

[0018] More preferably, the molar ratio of hydroquinone to 2-(2,6-dichlorophenyl)-3-phenylglutaronitrile is 1:1-4.

[0019] More preferably, the molar ratio of phenolsulfonphthalein to hydroquinone is 1:1-2.

[0020] More preferably, the usage ratio of N-methylpyrrolidone to 2-(2,6-dichlorophenyl)-3-phenylglutaronitrile is 1 mL: 1-3 mmol.

[0021] More preferably, the molar ratio of 2-(2,6-dichlorophenyl)-3-phenylglutaronitrile to anhydrous potassium carbonate is 1:1-4.

[0022] More preferably, the volume ratio of toluene to N-methylpyrrolidone is 1:1-5.

[0023] More preferably, the volume ratio of toluene to the precipitant is 1:5-10, the precipitant includes ethanol solution and dilute hydrochloric acid, the mass concentration of the ethanol solution is 70-100%, the concentration of the dilute hydrochloric acid is 0.2-2 mol / L, and the volume ratio of the ethanol solution to the dilute hydrochloric acid is 1:1-2.

[0024] Preferably, a method for preparing a sodium manganese titanium phosphate positive electrode material for a sodium ion battery comprises:

[0025] Sodium acetate, ammonium dihydrogen phosphate, polyethylene glycol and sucrose are mixed, deionized water is added for the first time, and high-speed stirring and dispersion is performed for 20-40 minutes, and then manganese acetate, titanium dioxide, calcium acetate, magnesium acetate, zinc oxalate, copper oxalate and aluminum nitrate are added, deionized water is added for the second time, and high-speed stirring and dispersion is performed for 20-40 minutes, and deionized water is added for the third time to adjust the solid content to 20-50wt%, and high-speed stirring and dispersion is performed again for 40-80 minutes, and the sand mill speed is 1000-3000 After sand grinding for 1-4 hours at rpm, spray drying is carried out, the inlet air temperature of spray drying is 150-250°C, the atomizer Hz is 200-400Hz, the feed rate is 2-5L / h, and then the temperature is increased to 500-800°C at a heating rate of 2-20°C / min. The dry powder precursor is calcined in a nitrogen atmosphere for 6-24 hours. After the material temperature is reduced to room temperature, a high entropy doped sodium manganese titanium phosphate positive electrode material for sodium ion batteries is obtained.

[0026] More preferably, the molar ratio of diammonium phosphate to sodium acetate is 1:1-6.

[0027] More preferably, the mass ratio of polyethylene glycol to diammonium phosphate is 1:1-5.

[0028] More preferably, the mass ratio of sucrose to polyethylene glycol is 1:1-2.

[0029] More preferably, the dosage ratio of sodium acetate to the first added deionized water is 1 mol: 300-500 mL.

[0030] More preferably, the molar ratio of sodium acetate to manganese acetate is 1:0.1-0.5.

[0031] More preferably, the molar ratio of titanium dioxide to manganese acetate is 1:0.5-1.0.

[0032] More preferably, the molar ratio of calcium acetate to manganese acetate is 1:40-50.

[0033] More preferably, the molar ratio of magnesium acetate to calcium acetate is 1:1-2.

[0034] More preferably, the molar ratio of zinc oxalate to calcium acetate is 1:1-2.

[0035] More preferably, the molar ratio of copper oxalate to calcium acetate is 1:1-2.

[0036] More preferably, the molar ratio of aluminum nitrate to calcium acetate is 1:1-2.

[0037] More preferably, the dosage ratio of titanium dioxide to the second added deionized water is 1 mol: 500-1000 mL.

[0038] Preferably, a method for preparing a sodium manganese titanium phosphate positive electrode material for a sodium ion battery comprises:

[0039] Sodium acetate, ammonium dihydrogen phosphate, polyethylene glycol and sucrose are mixed, deionized water is added for the first time, and high-speed stirring and dispersion is performed for 20-40 minutes, and manganese acetate, titanium dioxide, calcium acetate, magnesium acetate, zinc oxalate, copper oxalate and aluminum nitrate are added, deionized water is added for the second time, and high-speed stirring and dispersion is performed for 20-40 minutes, and deionized water is added for the third time to adjust the solid content to 20-50wt%, and a slurry binder is added, and high-speed stirring and dispersion is performed again for 40-80 minutes, and a sand mill speed of 1000- After sand grinding for 1-4 hours at 3000rpm, spray drying is carried out. The inlet air temperature of the spray drying is 150-250°C, the atomizer Hz is 200-400Hz, and the feed rate is 2-5L / h. The temperature is then increased to 500-800°C at a heating rate of 2-20°C / min. The dry powder precursor is calcined in a nitrogen atmosphere for 6-24 hours. After the material temperature is reduced to room temperature, a high entropy doped sodium manganese titanium phosphate positive electrode material for sodium ion batteries is obtained.

[0040] More preferably, the molar ratio of diammonium phosphate to sodium acetate is 1:1-6.

[0041] More preferably, the mass ratio of polyethylene glycol to diammonium phosphate is 1:1-5.

[0042] More preferably, the mass ratio of sucrose to polyethylene glycol is 1:1-2.

[0043] More preferably, the dosage ratio of sodium acetate to the first added deionized water is 1 mol: 300-500 mL.

[0044] More preferably, the molar ratio of sodium acetate to manganese acetate is 1:0.1-0.5.

[0045] More preferably, the molar ratio of titanium dioxide to manganese acetate is 1:0.5-1.0.

[0046] More preferably, the molar ratio of calcium acetate to manganese acetate is 1:40-50.

[0047] More preferably, the molar ratio of magnesium acetate to calcium acetate is 1:1-2.

[0048] More preferably, the molar ratio of zinc oxalate to calcium acetate is 1:1-2.

[0049] More preferably, the molar ratio of copper oxalate to calcium acetate is 1:1-2.

[0050] More preferably, the molar ratio of aluminum nitrate to calcium acetate is 1:1-2.

[0051] More preferably, the dosage ratio of titanium dioxide to the second added deionized water is 1 mol: 500-1000 mL.

[0052] More preferably, the slurry binder includes a polyarylethernitrile derivative, and the mass ratio of sodium acetate to the polyarylethernitrile derivative is 1:0.025-0.05.

[0053] Preferably, a method for preparing a sodium manganese titanium sodium phosphate positive electrode material for a sodium ion battery further uses a sodium sulfonate derivative as a slurry binder. The slurry binder includes a polyarylether nitrile derivative and a sodium sulfonate derivative, and the mass ratio of the polyarylether nitrile derivative to the sodium sulfonate derivative is 1:1. The sodium sulfonate derivative has a large number of hydrophilic groups, which interact with the surface of the active material particles to form an effective positive electrode electrolyte interface layer, which can further improve the electrochemical performance of the sodium ion battery positive electrode material, improve the first cycle reversible capacity of the sodium manganese titanium sodium phosphate positive electrode material for sodium ion batteries, and reduce the resistivity.

[0054] More preferably, the preparation of the sodium sulfonate derivative is specifically,

[0055] Weigh 11-bromocyclododecaneamide and tetraethylenepentamine, add anhydrous ethanol and stir to dissolve, react at 80-100°C for 5-15h, add sodium 8-chloronaphthalene-1-sulfonate and triethylamine, stir to react at 80-100°C for 1-5h, wash with acetone 2-5 times, and rotary evaporate to obtain a sodium sulfonate derivative.

[0056] More preferably, the molar ratio of tetraethylenepentamine to 11-bromocyclododecanoic acid amide is 1:1-5.

[0057] More preferably, the usage ratio of tetraethylenepentamine to anhydrous ethanol is 1 mol:15-60 mL.

[0058] More preferably, the molar ratio of tetraethylenepentamine to sodium 8-chloronaphthalene-1-sulfonate is 1:2-8.

[0059] More preferably, the molar ratio of tetraethylenepentamine to triethylamine is 1:0.001-0.004.

[0060] The invention also discloses the use of sodium manganese titanium phosphate positive electrode material for sodium ion batteries in the preparation of vehicles.

[0061] The present invention adopts a mixture of a sodium source, a phosphorus source, a carbon source, a titanium source, a manganese source and a high entropy metal source, and then adds a polyarylether nitrile derivative and a sodium sulfonate derivative as a slurry binder, and is sand-milled, spray-dried and calcined at high temperature to prepare a sodium ion battery manganese titanium sodium phosphate positive electrode material, so it has the following beneficial effects: the sodium ion battery manganese titanium sodium phosphate positive electrode material prepared by the present invention has good rate performance and cycle life, the first cycle reversible capacity is 85.6-105.3mAh / g, the resistivity is 5.08-5.61Ω·cm; the capacity retention rate is 100% when the cycle is 1000 times. Therefore, the present invention is a method for preparing a sodium ion battery manganese titanium sodium phosphate positive electrode material with high first cycle reversible capacity, low resistivity and long cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 This is the XRD pattern of the sodium manganese titanium phosphate positive electrode material prepared in Example 1.

[0063] Figure 2 This is the SEM image of the sodium manganese titanium phosphate positive electrode material prepared in Example 1.

[0064] Figure 3 This is the charge and discharge curve of the sodium manganese titanium phosphate positive electrode material prepared in Example 1.

[0065] Figure 4 This is a rate performance diagram of the sodium manganese titanium phosphate positive electrode material prepared in Example 1.

[0066] Figure 5 This is a cycle life diagram of the sodium manganese titanium phosphate positive electrode material prepared in Example 1. DETAILED DESCRIPTION

[0067] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0068] The experimental methods in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.

[0069] Embodiment 1:

[0070] S1. Preparation of sodium manganese titanium phosphate positive electrode material for sodium ion battery, comprising:

[0071] Sodium acetate, diammonium phosphate, polyethylene glycol and sucrose are mixed, deionized water is added for the first time, and the mixture is stirred and dispersed at high speed for 30 minutes. Manganese acetate, titanium dioxide, calcium acetate, magnesium acetate, zinc oxalate, copper oxalate and aluminum nitrate are then added, deionized water is added for the second time, and the mixture is stirred and dispersed at high speed for 30 minutes. Deionized water is added for the third time to adjust the solid content to 35wt%, and the mixture is stirred and dispersed at high speed for 60 minutes again. After sand milling for 1 hour at a sand milling speed of 2500rpm, spray drying is performed, and the inlet air temperature of the spray drying is 200°C, the hertz of the atomizer is 400Hz, and the feed rate is 3L / h. The temperature is then increased to 700°C at a heating rate of 5°C / min, and the dry powder precursor is calcined in a nitrogen atmosphere for 12 hours. After the material temperature is reduced to room temperature, a high entropy doped sodium manganese titanium phosphate positive electrode material for sodium ion batteries is obtained. The molar ratio of ammonium dihydrogen phosphate and sodium acetate is 1:3; the mass ratio of polyethylene glycol and ammonium dihydrogen phosphate is 1:2.3; the mass ratio of sucrose and polyethylene glycol is 1:1; the dosage ratio of sodium acetate and deionized water added for the first time is 1 mol:440 mL; the molar ratio of sodium acetate and manganese acetate is 1:0.3; the molar ratio of titanium dioxide and manganese acetate is 1:0.9; the molar ratio of calcium acetate and manganese acetate is 1:45; the molar ratio of magnesium acetate and calcium acetate is 1:1; the molar ratio of zinc oxalate and calcium acetate is 1:1; the molar ratio of copper oxalate and calcium acetate is 1:1; the molar ratio of aluminum nitrate and calcium acetate is 1:1; the dosage ratio of titanium dioxide and deionized water added for the second time is 1 mol:720 mL.

[0072] Embodiment 2:

[0073] S1. Preparation of polyarylethernitrile derivatives, comprising:

[0074] Weigh 2-(2,6-dichlorophenyl)-3-phenylglutaronitrile, hydroquinone and phenolsulfonphthalein, add N-methylpyrrolidone and stir evenly, then add anhydrous potassium carbonate and toluene, react at 150°C for 3h, rotary evaporate, react at 190°C for 5h, add a precipitant, precipitate a white solid, wash with deionized water 3 times, and vacuum dry to obtain a polyarylether nitrile derivative. The molar ratio of hydroquinone to 2-(2,6-dichlorophenyl)-3-phenylglutaronitrile is 1:2; the molar ratio of phenolsulfonphthalein to hydroquinone is 1:1; the dosage ratio of N-methylpyrrolidone to 2-(2,6-dichlorophenyl)-3-phenylglutaronitrile is 1mL:1.5mmol; the molar ratio of 2-(2,6-dichlorophenyl)-3-phenylglutaronitrile to anhydrous potassium carbonate is 1:2; the volume ratio of toluene to N-methylpyrrolidone is 1:2.5; the volume ratio of toluene to the precipitant is 1:7, the precipitant includes ethanol solution and dilute hydrochloric acid, the mass concentration of the ethanol solution is 95%, the concentration of the dilute hydrochloric acid is 1mol / L, and the volume ratio of the ethanol solution to the dilute hydrochloric acid is 1:1.

[0075] S2. Preparation of sodium manganese titanium phosphate positive electrode material for sodium ion battery, comprising:

[0076] Sodium acetate, diammonium phosphate, polyethylene glycol and sucrose are mixed, deionized water is added for the first time, and the mixture is stirred and dispersed at high speed for 30 minutes. Manganese acetate, titanium dioxide, calcium acetate, magnesium acetate, zinc oxalate, copper oxalate and aluminum nitrate are then added. Deionized water is added for the second time, and the mixture is stirred and dispersed at high speed for 30 minutes. Deionized water is added for the third time to adjust the solid content to 35wt%, and the polyarylether nitrile derivative prepared in step S1 is added, and the mixture is stirred and dispersed at high speed for 60 minutes again. After sand milling for 1 hour at a sand milling speed of 2500rpm, spray drying is performed, and the inlet air temperature of the spray drying is 200°C, the hertz of the atomizer is 400Hz, and the feed rate is 3L / h. The temperature is then increased to 700°C at a heating rate of 5°C / min. The dry powder precursor is calcined in a nitrogen atmosphere for 12 hours. After the material temperature is reduced to room temperature, a high entropy doped sodium manganese titanium phosphate positive electrode material for sodium ion batteries is obtained. The molar ratio of ammonium dihydrogen phosphate and sodium acetate is 1:3; the mass ratio of polyethylene glycol and ammonium dihydrogen phosphate is 1:2.3; the mass ratio of sucrose and polyethylene glycol is 1:1; the dosage ratio of sodium acetate and the first added deionized water is 1 mol:440 mL; the molar ratio of sodium acetate and manganese acetate is 1:0.3; the molar ratio of titanium dioxide and manganese acetate is 1:0.9; the molar ratio of calcium acetate and manganese acetate is 1:45; the molar ratio of magnesium acetate and calcium acetate is 1:1; the molar ratio of zinc oxalate and calcium acetate is 1:1; the molar ratio of copper oxalate and calcium acetate is 1:1; the molar ratio of aluminum nitrate and calcium acetate is 1:1; the dosage ratio of titanium dioxide and the second added deionized water is 1 mol:720 mL; the mass ratio of sodium acetate and the polyarylether nitrile derivative is 1:0.025.

[0077] Embodiment 3:

[0078] Compared with Example 2, the present embodiment differs in that in step S2, the sodium manganese titanium phosphate positive electrode material for sodium ion battery is prepared, except that the mass ratio of sodium acetate to the polyarylether nitrile derivative is changed to 1:0.01, and other conditions are the same as those in Example 2.

[0079] Embodiment 4:

[0080] S1. Preparation of polyarylethernitrile derivatives, comprising:

[0081] Weigh 2-(2,6-dichlorophenyl)-3-phenylglutaronitrile, hydroquinone and phenolsulfonphthalein, add N-methylpyrrolidone and stir evenly, then add anhydrous potassium carbonate and toluene, react at 150°C for 3h, rotary evaporate, react at 190°C for 5h, add a precipitant, precipitate a white solid, wash with deionized water 3 times, and vacuum dry to obtain a polyarylether nitrile derivative. The molar ratio of hydroquinone to 2-(2,6-dichlorophenyl)-3-phenylglutaronitrile is 1:2; the molar ratio of phenolsulfonphthalein to hydroquinone is 1:1; the dosage ratio of N-methylpyrrolidone to 2-(2,6-dichlorophenyl)-3-phenylglutaronitrile is 1mL:1.5mmol; the molar ratio of 2-(2,6-dichlorophenyl)-3-phenylglutaronitrile to anhydrous potassium carbonate is 1:2; the volume ratio of toluene to N-methylpyrrolidone is 1:2.5; the volume ratio of toluene to the precipitant is 1:7, the precipitant includes ethanol solution and dilute hydrochloric acid, the mass concentration of the ethanol solution is 95%, the concentration of the dilute hydrochloric acid is 1mol / L, and the volume ratio of the ethanol solution to the dilute hydrochloric acid is 1:1.

[0082] S2. Preparation of sodium sulfonate derivatives, comprising:

[0083] Weigh 11-bromocyclododecaneamide and tetraethylenepentamine, add anhydrous ethanol to stir and dissolve, react at 90℃ for 10h, add 8-chloronaphthalene-1-sulfonate sodium and triethylamine, stir and react at 85℃ for 3h, wash with acetone 3 times, and rotary evaporate to obtain sulfonic acid sodium salt derivative. The molar ratio of tetraethylenepentamine to 11-bromocyclododecaneamide is 1:2.4; the dosage ratio of tetraethylenepentamine to anhydrous ethanol is 1mol:30mL; the molar ratio of tetraethylenepentamine to 8-chloronaphthalene-1-sulfonate sodium is 1:4; the molar ratio of tetraethylenepentamine to triethylamine is 1:0.002.

[0084] S3. Preparation of sodium manganese titanium phosphate positive electrode material for sodium ion battery, comprising:

[0085] Sodium acetate, diammonium phosphate, polyethylene glycol and sucrose are mixed, deionized water is added for the first time, and the mixture is stirred and dispersed at high speed for 30 minutes. Manganese acetate, titanium dioxide, calcium acetate, magnesium acetate, zinc oxalate, copper oxalate and aluminum nitrate are then added, deionized water is added for the second time, and the mixture is stirred and dispersed at high speed for 30 minutes. Deionized water is added for the third time to adjust the solid content to 35wt%, and the polyarylether nitrile derivative prepared in step S1 and the sodium sulfonate derivative prepared in step S2 are added, and the mixture is stirred and dispersed at high speed for 60 minutes again. After sand milling for 1 hour at a sand milling speed of 2500rpm, spray drying is performed, and the inlet air temperature of the spray drying is 200°C, the hertz of the atomizer is 400Hz, and the feed rate is 3L / h. The temperature is then increased to 700°C at a heating rate of 5°C / min, and the dry powder precursor is calcined in a nitrogen atmosphere for 12 hours. After the material temperature is reduced to room temperature, a high entropy doped sodium manganese titanium phosphate positive electrode material for sodium ion batteries is obtained. The molar ratio of ammonium dihydrogen phosphate and sodium acetate is 1:3; the mass ratio of polyethylene glycol and ammonium dihydrogen phosphate is 1:2.3; the mass ratio of sucrose and polyethylene glycol is 1:1; the dosage ratio of sodium acetate and the first added deionized water is 1 mol:440 mL; the molar ratio of sodium acetate and manganese acetate is 1:0.3; the molar ratio of titanium dioxide and manganese acetate is 1:0.9; the molar ratio of calcium acetate and manganese acetate is 1:45; the molar ratio of magnesium acetate and calcium acetate is 1:1; the molar ratio of zinc oxalate and calcium acetate is 1:1; the molar ratio of copper oxalate and calcium acetate is 1:1; the molar ratio of aluminum nitrate and calcium acetate is 1:1; the dosage ratio of titanium dioxide and the second added deionized water is 1 mol:720 mL; the mass ratio of sodium acetate and the polyarylether nitrile derivative is 1:0.025; the mass ratio of the polyarylether nitrile derivative and the sodium sulfonate derivative is 1:1.

[0086] Embodiment 5:

[0087] Compared with Example 4, the present embodiment differs in that in step S3, in the preparation of sodium manganese titanium phosphate positive electrode material for sodium ion battery, except that the mass ratio of the polyarylether nitrile derivative and the sodium sulfonate derivative is changed to 1:0.5, other conditions are the same as those in Example 4.

[0088] Comparative Example 1:

[0089] S1. Preparation of sodium sulfonate derivatives, comprising:

[0090] Weigh 11-bromocyclododecaneamide and tetraethylenepentamine, add anhydrous ethanol to stir and dissolve, react at 90℃ for 10h, add 8-chloronaphthalene-1-sulfonate sodium and triethylamine, stir and react at 85℃ for 3h, wash with acetone 3 times, and rotary evaporate to obtain sulfonic acid sodium salt derivative. The molar ratio of tetraethylenepentamine to 11-bromocyclododecaneamide is 1:2.4; the dosage ratio of tetraethylenepentamine to anhydrous ethanol is 1mol:30mL; the molar ratio of tetraethylenepentamine to 8-chloronaphthalene-1-sulfonate sodium is 1:4; the molar ratio of tetraethylenepentamine to triethylamine is 1:0.002.

[0091] S2. Preparation of sodium manganese titanium phosphate positive electrode material for sodium ion battery, comprising:

[0092] Sodium acetate, diammonium phosphate, polyethylene glycol and sucrose are mixed, deionized water is added for the first time, and the mixture is stirred and dispersed at high speed for 30 minutes, and then manganese acetate, titanium dioxide, calcium acetate, magnesium acetate, zinc oxalate, copper oxalate and aluminum nitrate are added. Deionized water is added for the second time, and the mixture is stirred and dispersed at high speed for 30 minutes. Deionized water is added for the third time to adjust the solid content to 35wt%, and the sodium sulfonate derivative prepared in step S1 is added, and the mixture is stirred and dispersed at high speed for 60 minutes again. After sand milling for 1 hour at a sand milling speed of 2500rpm, spray drying is performed, and the inlet air temperature of the spray drying is 200°C, the hertz of the atomizer is 400Hz, and the feed rate is 3L / h. The temperature is then increased to 700°C at a heating rate of 5°C / min, and the dry powder precursor is calcined in a nitrogen atmosphere for 12 hours. After the material temperature is reduced to room temperature, a high entropy doped sodium manganese titanium phosphate positive electrode material for sodium ion batteries is obtained. The molar ratio of ammonium dihydrogen phosphate and sodium acetate is 1:3; the mass ratio of polyethylene glycol and ammonium dihydrogen phosphate is 1:2.3; the mass ratio of sucrose and polyethylene glycol is 1:1; the dosage ratio of sodium acetate and the first added deionized water is 1 mol:440 mL; the molar ratio of sodium acetate and manganese acetate is 1:0.3; the molar ratio of titanium dioxide and manganese acetate is 1:0.9; the molar ratio of calcium acetate and manganese acetate is 1:45; the molar ratio of magnesium acetate and calcium acetate is 1:1; the molar ratio of zinc oxalate and calcium acetate is 1:1; the molar ratio of copper oxalate and calcium acetate is 1:1; the molar ratio of aluminum nitrate and calcium acetate is 1:1; the dosage ratio of titanium dioxide and the second added deionized water is 1 mol:720 mL; the mass ratio of sodium acetate and the sodium sulfonate derivative is 1:0.025.

[0093] Experimental example:

[0094] Preparation of positive electrode sheet of battery: Sodium manganese titanium phosphate positive electrode material for sodium ion battery is mixed with acetylene black and N-methylpyrrolidone / polyvinylidene fluoride mixed solution, the obtained mixture is fully ground and mixed in a small mortar, 15 zirconium dioxide beads with a diameter of 3mm are added, and a mixed slurry is obtained by a micro vibration ball mill, which is coated on aluminum foil and placed in a vacuum drying oven at 120°C for vacuum drying for 12 hours. After the solvent is completely evaporated, the sheet is cut to obtain a positive electrode sheet of sodium ion battery. The N-methylpyrrolidone / polyvinylidene fluoride mixed solution includes polyvinylidene fluoride and N-methylpyrrolidone, and the volume ratio of polyvinylidene fluoride and N-methylpyrrolidone is 1g:20mL; the mass ratio of acetylene black and sodium manganese titanium phosphate positive electrode material for sodium ion battery is 1:31; the amount ratio of acetylene black and N-methylpyrrolidone / polyvinylidene fluoride mixed solution is 1g:1mL.

[0095] Assembly of sodium ion battery: Use the prepared sodium ion battery positive electrode sheet as the battery positive electrode, the glass fiber membrane as the separator, the sodium sheet as the battery negative electrode, the electrolyte includes sodium perchlorate, fluoroethylene carbonate and propylene carbonate, the dosage ratio of sodium perchlorate to propylene carbonate is 1 mol: 1L, the dosage ratio of fluoroethylene carbonate to propylene carbonate is 1 g: 20 mL, and assemble a button-type sodium ion battery.

[0096] 1. Material Characterization

[0097] At room temperature, the sodium manganese titanium sodium phosphate positive electrode material for sodium ion battery prepared in Example 1 was used to prepare a sodium ion battery positive electrode sheet, and the diffraction phenomenon in the sodium ion battery positive electrode sheet was tested by X-ray, using a copper target as the emission source, a scanning range of 10°-90°, a scanning speed of 5° / min, and a wavelength set to 0.15418nm.

[0098] At room temperature, a sodium ion battery positive electrode sheet was prepared using the sodium manganese titanium sodium phosphate positive electrode material for a sodium ion battery prepared in Example 1, and an energy spectrum test (SEM) was performed using a scanning electron microscope, with the acceleration voltage set to 10 kV.

[0099] Figure 1 The XRD pattern of the sodium manganese titanium phosphate positive electrode material prepared in Example 1. The diffraction peaks of Example 1 of the present invention are similar to those of Na 3 MnTi(PO 4 ) 3 There is no obvious difference in the standard diffraction peaks of , which indicates that the five high entropy metal ions doped in the present invention successfully replaced Na 3 MnTi(PO 4 ) 3 The central Mn and Ti atoms in the .

[0100] Figure 2This is a SEM image of the sodium manganese titanium phosphate positive electrode material prepared in Example 1. The sodium manganese titanium phosphate positive electrode material prepared in Example 1 of the present invention has an irregular shape.

[0101] 2. Electrochemical performance test

[0102] At room temperature, sodium ion batteries were assembled using the sodium manganese titanium sodium phosphate positive electrode materials prepared in Examples 1-5 and Comparative Example 1, and constant current charge and discharge tests, rate performance tests, and cycle life tests were performed on the sodium ion batteries prepared in Examples 1-5 and Comparative Example 1 in turn by using a Xinwei CT4000. In the constant current charge and discharge test, the test voltage window was 2.5-4.2V, and the current density was 0.02A / g; in the rate performance test, the current density was 0.02A / g, 0.1A / g, 0.2A / g, 0.5A / g, 1.0A / g, 2.0A / g, 3.0A / g, 4.0A / g, and 5.0A / g; in the cycle life test, the current density was 1A / g.

[0103] Figure 3 This is the charge and discharge curve of the sodium manganese titanium phosphate positive electrode material prepared in Example 1. The sodium manganese titanium phosphate positive electrode material prepared in Example 1 of the present invention has an obvious voltage platform in the first cycle; Figure 4 This is a rate performance diagram of the sodium manganese titanium phosphate positive electrode material prepared in Example 1. The sodium manganese titanium phosphate positive electrode material prepared in Example 1 of the present invention is cycled multiple times at different current densities. When the current density returns to 0.02 A / g, the reversible capacity is the same as the reversible capacity in the first cycle, indicating that it has good rate performance; Figure 5 This is a cycle life diagram of the sodium manganese titanium phosphate positive electrode material prepared in Example 1. The sodium manganese titanium phosphate positive electrode material prepared in Example 1 of the present invention has a reversible capacity of 85.6 mAh / g in the first cycle at a current density of 1 A / g, a reversible capacity of 85.6 mAh / g after 1000 cycles, and a capacity retention rate of 100%. This shows that the sodium manganese titanium phosphate positive electrode material prepared in Example 1 of the present invention has good rate performance and cycle stability.

[0104] Under the condition of a current density of 1.0 A / g, the first cycle reversible capacity of the sodium manganese titanium phosphate positive electrode materials for sodium ion batteries prepared in Examples 1-5 and Comparative Example 1 was measured. The measurement results are shown in Table 1.

[0105] Table 1 First cycle reversible capacity (mAh / g)

[0106]

[0107] As can be seen from Table 1, the first cycle reversible capacity of Example 2-3 is higher than that of Example 1 because, in the preparation of sodium manganese titanium phosphate positive electrode material for sodium ion battery, Examples 2-3 additionally use polyarylether nitrile derivatives as slurry binders, while no polyarylether nitrile derivatives are used in Example 1; the first cycle reversible capacity of Example 2 is higher than that of Example 3 because the amount of polyarylether nitrile derivatives used in the preparation of sodium manganese titanium phosphate positive electrode material for sodium ion battery is different. This shows that the present invention uses polyarylether nitrile derivatives as slurry binders in the preparation of sodium manganese titanium phosphate positive electrode material for sodium ion battery, which can effectively improve the first cycle reversible capacity of sodium manganese titanium phosphate positive electrode material for sodium ion battery.

[0108] The first cycle reversible capacity of Examples 4-5 is higher than that of Examples 2 and Comparative Example 1 because, in the preparation of sodium manganese titanium phosphate positive electrode materials for sodium ion batteries, Examples 4-5 use polyarylether nitrile derivatives and sodium sulfonate derivatives as slurry binders, while Example 2 only uses polyarylether nitrile derivatives as slurry binders, and Comparative Example 1 only uses sodium sulfonate derivatives as slurry binders; the first cycle reversible capacity of Example 4 is higher than that of Example 5 because the amount of sodium sulfonate derivatives used in the preparation of sodium manganese titanium phosphate positive electrode materials for sodium ion batteries is different. This shows that the present invention further uses polyarylether nitrile derivatives as slurry binders in the preparation of sodium manganese titanium phosphate positive electrode materials for sodium ion batteries, which can further improve the first cycle reversible capacity of sodium manganese titanium phosphate positive electrode materials for sodium ion batteries.

[0109] 3. Resistivity

[0110] The resistivity of the positive electrode sheets prepared in Examples 1-5 and Comparative Example 1 was tested using a BER1300 multifunctional electrode sheet resistance meter. Resistivity (Ω·cm) = cross-sectional area of ​​the positive electrode sheet (cm 2 )×resistance (Ω) / electrode length (cm). The resistivity measurement results are shown in Table 2.

[0111] Table 2 Resistivity (Ω·cm)

[0112]

[0113] As can be seen from Table 2, the resistivity of Example 2-3 is lower than that of Example 1 because, in the preparation of the sodium manganese titanium phosphate positive electrode material for sodium ion batteries, Examples 2-3 additionally use polyarylether nitrile derivatives as slurry binders, while no polyarylether nitrile derivatives are used in Example 1; the resistivity of Example 2 is lower than that of Example 3 because the amounts of polyarylether nitrile derivatives used in the preparation of the sodium manganese titanium phosphate positive electrode material for sodium ion batteries are different. This shows that the present invention uses polyarylether nitrile derivatives as slurry binders in the preparation of the sodium manganese titanium phosphate positive electrode material for sodium ion batteries, which can effectively reduce the resistivity of the sodium manganese titanium phosphate positive electrode material for sodium ion batteries, thereby improving its electronic conductivity.

[0114] The resistivity of Examples 4-5 is lower than that of Examples 2 and Comparative Example 1 because, in the preparation of sodium manganese titanium phosphate positive electrode materials for sodium ion batteries, Examples 4-5 use polyarylether nitrile derivatives and sodium sulfonate derivatives as slurry binders, while Example 2 only uses polyarylether nitrile derivatives as slurry binders, and Comparative Example 1 only uses sodium sulfonate derivatives as slurry binders; the resistivity of Example 4 is lower than that of Example 5 because the amount of sodium sulfonate derivatives used in the preparation of sodium manganese titanium phosphate positive electrode materials for sodium ion batteries is different. This shows that the present invention further uses polyarylether nitrile derivatives as slurry binders in the preparation of sodium manganese titanium phosphate positive electrode materials for sodium ion batteries, which can further reduce the resistivity of sodium manganese titanium phosphate positive electrode materials for sodium ion batteries, thereby improving their electronic conductivity.

[0115] The conventional operations in the operating steps of the present invention are well known to those skilled in the art and will not be described in detail here.

[0116] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a sodium manganese titanium sodium phosphate positive electrode material for a sodium ion battery, comprising: mixing a sodium source, a phosphorus source, a carbon source, a titanium source, a manganese source and a high entropy metal source, adding a slurry binder, stirring and dispersing at high speed, and preparing a sodium manganese titanium sodium phosphate positive electrode material for a sodium ion battery through sand milling, spray drying and high-temperature calcination; the slurry binder comprises at least a polyarylether nitrile derivative, and the polyarylether nitrile derivative has a sulfur element and a cyano group; in the preparation of the polyarylether nitrile derivative, 2-(2,6-dichlorophenyl)-3-phenylglutaronitrile reacts with hydroquinone and phenolsulfonphthalein to obtain a polyarylether nitrile derivative; the molar ratio of the hydroquinone to 2-(2,6-dichlorophenyl)-3-phenylglutaronitrile is 1:1-4, and the molar ratio of the phenolsulfonphthalein to the hydroquinone is 1:1-2.

2. The method for preparing a sodium manganese titanium phosphate positive electrode material for a sodium ion battery according to claim 1, characterized in that: The sodium source is sodium acetate, the phosphorus source is ammonium dihydrogen phosphate, and the molar ratio of the phosphorus source to the sodium source is 1:1-6.

3. The method for preparing a sodium manganese titanium phosphate positive electrode material for a sodium ion battery according to claim 1, characterized in that: The carbon source comprises polyethylene glycol and sucrose, and the mass ratio of sucrose to polyethylene glycol is 1:1-2.

4. The method for preparing a sodium manganese titanium phosphate positive electrode material for a sodium ion battery according to claim 1, characterized in that: The manganese source is manganese acetate, the titanium source is titanium dioxide, and the molar ratio of the titanium source to the manganese source is 1:0.5-1.

0.

5. The method for preparing a sodium manganese titanium phosphate positive electrode material for a sodium ion battery according to claim 1, characterized in that: The high entropy metal source includes calcium acetate, magnesium acetate, zinc oxalate, copper oxalate and aluminum nitrate.

6. The method for preparing a sodium manganese titanium phosphate positive electrode material for a sodium ion battery according to claim 1, characterized in that: In the sand milling process, the sand milling speed is 1000-3000 rpm and the processing time is 1-4 hours.

7. The method for preparing a sodium manganese titanium phosphate positive electrode material for a sodium ion battery according to claim 1, characterized in that: In the spray drying, the air inlet temperature is 150-250° C., the atomizer frequency is 200-400 Hz, and the feed rate is 2-5 L / h.

8. The method for preparing a sodium manganese titanium phosphate positive electrode material for a sodium ion battery according to claim 1, characterized in that: In the high temperature calcination, the calcination temperature is 500-800° C. and the calcination time is 6-24 hours.

9. Use of the sodium manganese titanium phosphate positive electrode material for sodium ion batteries prepared by any method of claims 1 to 8 in the preparation of vehicles.

Citation Information

Patent Citations

  • Delocalized anions for use as electrolytic solutes

    CA2194127A1

  • Sodium vanadium titanium phosphate fluoride / carbon composite material for sodium-ion battery and preparation method thereof

    CN110556518A